Investigation of eight-arm tapered star copolymers prepared by anionic copolymerization and coupling reaction. Issue 26 (24th June 2022) - Wang, Chengmeng; Wu, Yibo; Zhu, Yihui; Ma, Hongbing; Zhang, Mingzu; Liu, GengXin; He, Jinlin; Ni, Peihong
Abstract : A series of eight-arm tapered star copolymers 8[P(I- co -S) x ]-POSS were synthesized by the coupling reaction between octavinyl POSS and the tapered living copolymer chains obtained from statistical anionic copolymerization. Abstract : A tapered copolymer is one kind of copolymer with unique microstructure, whereas a multi-arm tapered star copolymer has been rarely studied possibly due to the synthetic challenge. Herein, this work focuses on the investigation of eight-arm tapered star copolymers. Firstly, several tapered linear copolymers were prepared by the statistical anionic copolymerization of isoprene and styrene based on their reactivity difference in non-polar solvents. The tapered microstructures were confirmed by several techniques including proton nuclear magnetic resonance ( 1 H NMR), gel permeation chromatography (GPC), matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS), and real-time 1 H NMR. Next, the tapered and diblock copolymers with similar molecular weight and volume fraction of PS were synthesized to compare the property difference by using thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and rheology characterization. Moreover, the tapered linear copolymers with different ratios of soft and hard blocks were prepared by changing the feed ratios of the two monomers. It is found that the ratio of the soft and hard segments affects the thermal and mechanical properties of tapered copolymers to a large extent. Finally, octavinyl polyhedral oligomeric silsesquioxane (OVPOSS) was introduced as a coupling agent to directly react with the tapered living copolymer chain, yielding three kinds of eight-arm tapered star copolymers 8[P(I- co -S) x ]-POSS ( x = 1, 2, and 3) with different numbers of tapered blocks. The chemical structures and molecular weights of the resultant star copolymers were characterized. Furthermore, the results indicated that the introduction of the star-shaped structure could increase the thermal stability, while the increase of tapered block numbers might result in distinct thermal and viscoelastic behaviors of the copolymers.